Relation between agenesis and shape anomaly of maxillary lateral incisors and canine impaction - Anísio Bueno de Carvalho; Rogério Heladio Lopes Motta; Eliane Maria Duarte de Carvalho (Dental Press Editora, 2012)
OBJECTIVE: The purpose was to obtain information about the relation between agenesis and shape anomaly of maxillary lateral incisors and canine impaction. METHODS: Seventy-three patients with canine impaction and 73 control patients, without canine impaction, were evaluated. The mesiodistal distances of the maxillary lateral incisors adjacent to the impacted canines and the correspondent mandibular lateral incisors were measured. The adjacent lateral incisors were classified in: 1 - absent, 2 - small, 3 - peg-shaped, 4 - standard. RESULTS: The results showed that among the patients with impacted canines, there were 21 anomalous teeth (small and peg-shaped) and among the control patients there were only three small and peg-shaped teeth, with a statistically significant difference (p = 0.001). No patients were found with impacted canines and absent lateral incisors. CONCLUSION: It was concluded that in patients with anomalous lateral incisors (small and peg-shaped) there is a probability to present impacted canines and this must be considered. OBJETIVO: o objetivo foi obter informação sobre a relação existente entre a agenesia e/ou anomalia de forma de incisivos laterais superiores e impacção de caninos. MÉTODOS: foram avaliados 73 pacientes com impacção de caninos e 73 pacientes controle, sem impacção de caninos. Foram medidas as distâncias mesiodistais dos incisivos laterais superiores adjacentes aos caninos impactados e os incisivos laterais correspondentes inferiores. Os incisivos laterais adjacentes foram classificados em: 1 - ausentes; 2 - pequenos; 3 - conoides; 4 - normais. RESULTADOS: os resultados mostraram que no grupo de pacientes com caninos impactados foram encontrados 22 dentes anômalos (pequenos e conoides), e no grupo controle apenas três dentes pequenos e conoides, sendo uma diferença estatisticamente significativa (p=0,001). Não foram encontrados pacientes com canino impactado e incisivo lateral ausente. CONCLUSÃO: concluiu-se que nos pacientes com incisivos laterais anômalos (pequenos e conoides), a probabilidade de apresentarem caninos impactados existe e deve ser considerada.